Genetic structure and diversity of South Africa's inshore Bryde's whale (Balaenoptera edeni brydei, Olsen 1913) population - Bloomer, Paulette (University of Pretoria, 2023)
Dissertation (MSc (Zoology))--University of Pretoria, 2022.